School Attendance Problems in Scotland and Spain: Variations in Recording, Reporting, and Using Data - Mariola Giménez-Miralles; Carolina Gonzálvez; Markus Klein; Edward Sosu (Karolinum Press, 2023)
School attendance problems (SAPs) are a worldwide concern due to their significant impact on students' development. SAPs may vary across countries depending on the effectiveness of policy measures for prevention and care, the functioning of the educational systems, and the cultural and social environments, among others. According to the latest PISA results, 6.5% of Spanish students were absent from school once or twice per week. In Scotland, school absence rates increased from 7% to 8% from the 2018−2019 to 2020−2021 academic year even after accounting for COVID-19 related absences. This paper draws on official documents and statistics to investigate SAPs in Spain and Scotland, considering differences in the structure of the education system, approaches to recording absences in schools, strengths, and weaknesses of each system. It sets the scene by describing the educational context, the conceptualization of absenteeism, recording procedures, reporting issues and data in Spain and Scotland. The paper demonstrates that these countries have different ways of reporting and making this information available. Finally, comments on lessons learned and suggestions for policy and research relating to absenteeism are considered.